Income Transfers and Assets of the Poor - Ziliak, James P. (The Review of Economics and Statistics, 2003)
Contrary to the predictions of the standard life-cycle model, many low-lifetime-income households accumulate little wealth relative to their incomes compared to households with high lifetime income. I use data from the Panel Study of Income Dynamics and a correlated random-effects generalized-method-of-moments estimator to decompose the rich-poor gaps in wealth-to-permanent-income ratio into the portions attributable to differences in characteristics such as labor market earnings, income uncertainty, observed demographics, and the utilization of transfer programs which may have stringent income and liquid-asset tests, and those attributable to differences in the estimated coefficients on the respective characteristics. The results suggest that wealth-to-permanent-income ratios are increasing in permanent labor income and income uncertainty, but that transfer income, with or without asset tests, discourages liquid-asset accumulation. The decompositions indicate that most of the rich-poor wealth gap is attributable to differences in average characteristics and not coefficients. The leading factor driving the gap between the rich and poor in the ratio of liquid wealth to permanent income is asset-tested transfer income, whereas the leading factor driving the gap in the ratio of net worth to permanent income is labor-market earnings.